MANAGEMENT ACCOUNTING TOOLS TRANSFORMATION FOR THE NEEDS OF ENTERPRISE MANAGERS UNDER MARTIAL LAW IN UKRAINE - Ljudvenko, Dmytro; Khomovyi, Sergey; Tomilova-Yaremchuk, Nadiia; Vakulenko, Vitalii; Khomovyi, Mykhailo (Scientific Journal of Polonia University, 2023)
The main purpose of this article is to analyze and research the main tools of management accounting functioning, identify trends of their future development and optimize processes improving its information content for managers based on the changes that are taking place in the current conditions of martial law in Ukraine. The analysis of the features of economic processes was carried out using the principles of dialectics, which allowed to classify the effects of the crisis processes of the Ukrainian economy. The classification of the effects of the crisis processes of the Ukrainian economy associated with the introduction of martial law is carried out and their impact on the development of management accounting tools was shown. The main functions of management accounting, which characterize the depressive phenomena of the economy and have a direct impact on its functioning, are highlighted. Based on the highlighted functions, we have adjusted the objects and tasks facing management accounting during martial law. The conceptual anti-crisis model of management accounting was formed, its functional variability determines the set of objects of management accounting, which is mainly associated with the need to manage the parameters of strategic anti-crisis development of the economic entity, as well as monitoring and control of its detailed microenvironment under martial law. The results of the study have important practical value for managers of enterprises that are affected by crisis phenomena caused by rapid negative changes in the external environment.